(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article highlights importance of strategies and features in reading classes, levels of reading comprehension and stages of reading strategies and why to use interactive activities in reading classes in higher educational organization.